THE IMPORTANCE OF EMOTIONAL MANAGEMENT IN ADOLESCENT LIFE. (Universal International Scientific Journal, 2026)
This article analyzes the role of emotional intelligence in psychological adjustment, learning motivation, and social relationship stability during adolescence. The data are interpreted based on theoretical analysis and comparison.
Keywords: emotional intelligence, adolescence, emotion management, self-awareness, empathy, social adjustment, school environment